2008
DOI: 10.1007/s11695-008-9719-0
|View full text |Cite
|
Sign up to set email alerts
|

Video-Assisted Versus Conventional Tracheal Intubation in Morbidly Obese Patients

Abstract: Because LMA CTrach promoted short apnea time and the Airtraq laryngoscope allowed early definitive airway, both video-assisted tracheal intubation devices prevented most serious arterial oxygenation desaturation evidenced during tracheal intubation of morbidly obese patients with the conventional Macintosh laryngoscope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 14 publications
3
63
0
2
Order By: Relevance
“…Intubation times were shortest with the Airtraq, followed by the Macintosh, and the CTrach. 90 In addition, more patients in the Airtraq and CTrach groups maintained oxygen saturation [ 92%, and fewer patients in these groups desaturated to \ 88%.…”
Section: Airway Managementmentioning
confidence: 92%
“…Intubation times were shortest with the Airtraq, followed by the Macintosh, and the CTrach. 90 In addition, more patients in the Airtraq and CTrach groups maintained oxygen saturation [ 92%, and fewer patients in these groups desaturated to \ 88%.…”
Section: Airway Managementmentioning
confidence: 92%
“…In a study comparing videoassisted with direct laryngoscopy in 318 morbidly obese patients, the Airtraq TM and LMA CTrach TM provided an earlier definitive airway and shortest apnea time, respectively, when compared with the conventional Macintosh laryngoscope. 41 Video-assisted techniques resulted in significantly better percentage of glottis opening (POGO) scores compared with direct laryngoscopy (97% vs 75%, respectively; P \ 0.01). Andersen et al also found that the Glidescope Ò video laryngoscope provided better glottic views and lower intubation difficulty scores when compared with the Macintosh laryngoscope in morbidly obese patients.…”
Section: Direct Vs Indirect Laryngoscopymentioning
confidence: 96%
“…Dans une étude comparant la vidéolaryngoscopie à la laryngoscopie directe chez 318 patients obèses morbides, le Airtraq TM et le masque laryngé CTrach TM ont fourni un accès définitif aux voies aériennes plus rapidement et un temps d'apnée plus court, respectivement, que le laryngoscope conventionnel Macintosh. 41 Lors du recours aux techniques assistées par vidéo, les scores d'ouverture glottique (POGO) étaient significativement plus élevés que lors de l'utilisation de la laryngoscopie directe (97 % vs. 75 %, respectivement; P \ 0,01). Andersen et coll.…”
Section: Choix De La Technique D'intubationunclassified
“…[12][13][14] Head and neck positions are especially important and sniff and ramp positions should be maintained throughout the operation. [15][16][17][18] Patients with obesity hypoventilation syndrome should be evaluated with arterial blood gases, respiratory function tests, and echocardiography as needed, and postoperative CPAP use should be discussed if necessary.…”
Section: Preoperative Preparation Of the Morbidly Obese Patientmentioning
confidence: 99%